Low attentional engagement makes attention network activity susceptible to emotional interference - Exposito, Veronica (2014)
The aim of this study was to investigate whether emotion-attention interaction depends on attentional engagement. To investigate emotional modulation of attention network activation, we used a functional MRI paradigm consisting of a visuospatial attention task with either frequent (high-engagement) or infrequent (low-engagement) targets and intermittent emotional or neutral distractors. The attention task recruited a bilateral frontoparietal network with no emotional interference on network activation when the attentional engagement was high. In contrast, when the attentional engagement was low, the unpleasant stimuli interfered with the activation of the frontoparietal attention network, especially in the right hemisphere. This study provides novel evidence for low attentional engagement making attention control network activation susceptible to emotional interference. © 2014 Wolters Kluwer Health | Lippincott Williams & Wilkins.